The fate of iron during the alkali‐activation of synthetic (CaO‐)FeOx‐SiO2 slags: An Fe K‐edge XANES study. Issue 5 (1st December 2017) - Simon, Sebastian; Gluth, Gregor J. G.; Peys, Arne; Onisei, Silviana; Banerjee, Dipanjan; Pontikes, Yiannis
Abstract: Slags from the nonferrous metals industry have great potential to be used as feedstocks for the production of alkali‐activated materials. Until now, however, only very limited information has been available about the structural characteristics of these materials. In the work presented herein, synthetic slags in the CaO–FeO x –SiO2 system, representing typical compositions of Fe‐rich slags, and inorganic polymers (IPs) produced from the synthetic slags by activation with alkali silicate solutions have been studied by means of X‐ray absorption near‐edge structure (XANES) spectroscopy at the Fe K ‐edge. The iron in the slags was largely Fe 2+, with an average coordination number of approximately 5 for the iron in the amorphous fraction. The increase in average oxidation number after alkali‐activation was conceptualized as the consequence of slag dissolution and IP precipitation, and employed to calculate the degrees of reaction of the slags. The degree of reaction of the slags increased with increasing amorphous fraction. The iron in the IPs had an average coordination number of approximately 5; thus, IPs produced from the Fe‐rich slags studied here are not Fe‐analogs of aluminosilicate geopolymers, but differ significantly in terms of structure from the latter.